Implementation of Maqâshid Al-Shari'ah in The Profit Distribution System of Islamic Banking in Indonesia - Ismiati, Baiq (Citizen : Jurnal Ilmiah Multidisiplin Indonesia, 2025)
This study aims to analyze the implementation of maqâshid al-syari’ah in the profit distribution system of Islamic banking in Indonesia. The primary focus of this research is to examine how Sharia principles are applied in the profit-sharing mechanism and their impact on transparency, fairness, and financial inclusion. The study employs a qualitative approach through interviews with Islamic banking practitioners, regulators, and academics. The findings reveal that the application of maqâshid al-syari’ah has enhanced transparency and fairness in profit distribution. However, several challenges remain, including limited public understanding of the profit-sharing concept, regulatory dualism with the conventional banking system, and constraints in financial product innovation. Addressing these challenges requires synergy between the government, banking institutions, and academia to strengthen policies, improve Islamic financial literacy, and develop financial products aligned with maqâshid al-syari’ah. By doing so, Islamic banking can become more competitive and contribute to national economic growth.